Enhanced Fluorescence Quenching of 2‐Thiohydantoin‐Containing Conjugated Polymers: Applications for Ion Sensing. Issue 14 (3rd June 2014) - Zeng, Weifeng; Yong, Xue; Yang, Xiaodong; Yan, Yichen; Lu, Xinwei; Qu, Jinqing; Liu, Ruiyuan
<x xml:space="preserve">Abstract</x> A novel poly(phenylene ethynylene) containing 2‐thiohydantoin [poly(1)] is synthesized. The addition of F− quenches the fluorescence, while the fluorescence of the solution only changes slightly upon addition of other anions, indicating the sensing ability of poly(1) toward F−. The addition of Ag+ quenches the fluorescence of the polymer, whereas the addition of other metal ions results in only slight changes to the fluorescence. Compared with its small‐molecule counterpart, the Stern–Volmer quenching constants of poly(1) toward F− and Ag+ are 165 and 105 times greater, respectively. This result indicates the amplified quenching effect of poly(1). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>